Морфология яиц клопов-хшцнецов (Heteroptera, Reduviidae) европейской части СССР - Пучков, П.В. (Вестник зоологии, 1981)
The paper describes eggs of 20 species of Reduviidae (Heteroptera) from European part of the USSR. Harpactorinaeare notincluded. Characters of eggs o fsomespecies are as tollows: rygolampis bidentala-cap with circular row of those or the collar resembles egg or kasanus ougurlarus. Neither centre of the cap, nor its filaments reachthe collar-margin. O. brachymerus - cap filaments reach or extend collar-margin. 1.0-1.2 mm. O. simillimus ~- as previous. but 1.4-1.6 mm. O. squalidus - cap lilaments imperceptible, the centre of the cap is elevated overcollar. Ectomocoriscaucasicus-contraryto ululansthecanprocessissudequal to the collar in height, its outer diameter only 1.1-1.4 times smaller than the neck-width. rastra bastolera- caD is utterey covered witn porous white substance superoperculum with low small and obtuse central elevation. Holotrichius apterus - wax-likesuperoper- culum covers the periphery of thecap, depression for immobilization is present. Reduvius restaceus- cap w i n rougn reaculaton, choron practicassy S T O O L S ciliatus- practi- cally smooth, with depression of immobilization. R. personatus- such depression is ab- sent, chorion finely reticulated, 1.45-1.7 mm long.Metapterus linearis- like Barce fra- terna, but cap-projection is small. Empicoris culcuormas - contrary to previous descriptions chorion brown. ridges of ovocement are fringed or ciliated.